2008
DOI: 10.1177/0264619607083835
|View full text |Cite
|
Sign up to set email alerts
|

Patient profile and management in advanced glaucoma

Abstract: Purpose: to study patient characteristics and management profile in advanced glaucoma. Method: A retrospective study of 87 case notes of patients registered blind due to glaucoma, and cross-sectional interview of 29 patients. Results: advanced glaucoma at presentation was documented in 43 cases (49%). Insufficient optometry assessment was significantly associated with advanced disease (p = 0.0339). Normal tension glaucoma patients were significantly more likely to present with advanced disease compared to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This suggests that ophthalmologists should consider whether some patients with NTG might benefit from formal assessment by mental health services. visual field defect in at least on eye at presentation, which is in agreement with previous studies showing patients with NTG are more likely to present with advanced disease [30]. It has also been shown that factors including older age, African ancestry and socioeconomic deprivation are associated with delayed presentation [31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that ophthalmologists should consider whether some patients with NTG might benefit from formal assessment by mental health services. visual field defect in at least on eye at presentation, which is in agreement with previous studies showing patients with NTG are more likely to present with advanced disease [30]. It has also been shown that factors including older age, African ancestry and socioeconomic deprivation are associated with delayed presentation [31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…The challenge of professionals having to explain complex information is no doubt increased as the patients are often in a state of shock having received bad news, and this may be compounded further as many also have health and/or communication difficulties in addition to their visual impairment (70% reporting this to be the case, and many reported hearing difficulties). Possible other evidence for this difficulty was found in a recent study of patients attending a hospital‐based glaucoma clinic which noted that poor compliance with medication was significantly higher in those with hearing loss (Wallace et al. , 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Whilst it is uncertain whether surgical management impacts PGA prescribing in areas of deprivation, there is evidence patient adherence may be influential. A study looking at demographics of patients registered severely sight impaired from glaucoma 18 found those with advanced disease and those with poor adherence were more likely to have greater deprivation. Arguably the corollary is increased sight testing in affluent areas generates more glaucoma referrals and greater repeat prescribing within primary care.…”
Section: Strengths and Limitationsmentioning
confidence: 99%